Hitchhiking probiotic vectors to deliver ultra-small hafnia nanoparticles for 'Color' gastrointestinal tract photon counting X-ray imaging. Issue 5 (21st March 2022) - Ostadhossein, Fatemeh; Moitra, Parikshit; Gunaseelan, Nivetha; Nelappana, Michael; Lowe, Chiara; Moghiseh, Mahdieh; Butler, Anthony; de Ruiter, Niels; Mandalika, Harish; Tripathi, Indu; Misra, Santosh K.; Pan, Dipanjan
Abstract : Gastrointestinal (GI) tract is one of the hard-to-reach target tissues for the delivery of contrast agents and drugs. Herein we have used novel hafnia nanoparticles encapsulated in probiotics for GI tract imaging using photon counting color-CT. Abstract : Gastrointestinal (GI) tract is one of the hard-to-reach target tissues for the delivery of contrast agents and drugs mediated by nanoparticles due to its harsh environment. Herein, we overcame this barrier by designing orally ingestible probiotic vectors for 'hitchhiking' ultrasmall hafnia (HfO2 ) (∼1–2 nm) nanoparticles. The minute-made synthesis of these nanoparticles is accomplished through a simple reduction reaction. These nanoparticles were incubated with probiotic bacteria with potential health benefits and were non-specifically taken up due to their small size. Subsequently, the bacteria were lyophilized and packed into a capsule to be administered orally as the radiopaque contrast agents for delineating the GI features. These nano-bio-hybrid entities could successfully be utilized as contrast agents in vivo in the conventional and multispectral computed tomography (CT). We demonstrated in 'color' the accumulated nanoparticles using advanced detectors of the photon counting CT. The enhanced nano-bio-interfacing capability achieved here can circumvent traditional nanoparticle solubility and delivery problems while offering a patient friendly approach for GI imaging to replace the currently practiced barium meal.